2008
DOI: 10.2190/cs.10.3.b
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Part-Time Faculty on First Semester Freshmen Retention: A Predictive Model Using Logistic Regression

Abstract: Part-time faculty clearly serve a valuable purpose in higher education; however, their increased use raises concerns for administrators, faculty, and policy makers. Part-time faculty members spend a greater proportion of their overall time teaching, but the initial evidence suggests that these instructors are less available to students and are less engaged with the campus environment. Recent research attempts to connect part-time faculty utilization to student outcomes. This study explored the effects of expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 25 publications
4
33
1
Order By: Relevance
“…These findings are not surprising given that contingent faculty often lack adequate office space, access to computers on campus, and workshops in the use of teaching with technology. These results showed contingent faculty are less likely to be engaged with students outside of the classroom, consistent with Jaeger (2008). She found that although part-time faculty are often unavailable for advising, committee work, and other non-instructional duties, this is also not part of their assignment.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…These findings are not surprising given that contingent faculty often lack adequate office space, access to computers on campus, and workshops in the use of teaching with technology. These results showed contingent faculty are less likely to be engaged with students outside of the classroom, consistent with Jaeger (2008). She found that although part-time faculty are often unavailable for advising, committee work, and other non-instructional duties, this is also not part of their assignment.…”
Section: Discussionsupporting
confidence: 61%
“…The large proportion of non tenure-track faculty primarily teaching undergraduate level classes may raise questions regarding the type of instruction graduate or professional courses taught and students are receiving in foundation courses. For example, two studies showed that new college students had more than 25% of their academic credits taught by contingent faculty and students taught by contingent faculty had a reduced likelihood of persisting to the second semester (Harrington & Schibik, 2004;Jaeger & Hinz, 2008). Faculty who teach foundation and general education courses can enrich or diminish student learning by the attitudes, beliefs, and skills they have as teachers (Meacham, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations